On the disunity of the sciences and Ceteris Paribus laws - Tobin, Emma (Trinity College (Dublin, Ireland). Philosophy Department, 2006)
This thesis examines the claim that the sciences are disunified. Chapter 1 outlines and introduces different accounts of the stratification of the sciences in the literature, in particular, Unificationism, Disunificationism, Eliminativism and Human Science Disunificationism. I argue that all of these competing views are informed by an ideal model for successful science. In particular, all of the views discussed are committed to the claim that a science requires laws to be considered scientifically legitimate. At the end of this chapter, the narrower topic of the thesis is revealed: do the special sciences have real legitimate ceteris paribus laws?
Keywords: Philosophy, Ph.D.; Ph.D. Trinity College Dublin